Ketogenic Diet: Effects on Growth - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of the ketogenic diet on growth of 237 children (130 males, 107 females) treated for intractable epilepsy has been evaluated in a prospective cohort study (average follow-up 308 days) at the Johns Hopkins Hospital, Baltimore, MD.